Penerapan Model Pembelajaran Cooperati Learning Dalam Meningkatkan Hasil Belajar Pada Mata Pelajaran PAI - Surtinah, Surtinah; Batu Bara , Samro; Hermawati, Hermawati (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes of Islamic Education (PAI) for fourth-grade students at SMP Negeri 2 Kubu through the implementation of the Cooperative Learning model. Identified problems include low student participation in the learning process, limited comprehension of material, and lack of learning motivation. This research uses a Classroom Action Research (CAR) approach conducted in several cycles. The results indicate that the application of Cooperative Learning can enhance student learning outcomes in cognitive, affective, and psychomotor aspects. Furthermore, the study identifies several challenges in implementing this model, such as time management and varying levels of student engagement. Nevertheless, Cooperative Learning has advantages in enhancing critical thinking, collaboration, and learning motivation. Thus, this model can be an effective solution in PAI learning to improve the quality of student learning outcomes.